COMPARISON OF LEVELS OF PHYSICAL FITNESS BETWEEN HYPERTENSIVE AND NORMOTENSIVE INDIVIDUALS - Bottcher, Lara Belmudes; Kokubun, Eduardo [UNESP] (Soc Brasileira Med Esporte, 2017)
Introduction: Hypertension is a major risk factor for morbidity and mortality caused by cardiovascular diseases. Studies indicate an inverse relationship between mortality rate and physical fitness level. Objective: To determine if there are differences in physical fitness between hypertensive and normotensive individuals and whether there is an effect of regular physical activity on physical fitness in hypertensive similar to that found in normotensive individuals. Methods: The study included 214 women (>= 40 years), who were part of a physical activity program for 6 months. All subjects were submitted to an anthropometric and physical fitness assessment (AAHPERD). Results: Hypertensive individuals have a worse initial condition in relation to agility (GH initial mean = 24.2 +/- 0.4 sec. and GN = 20.9 +/- 0.8 sec., p<0.01), coordination (GH initial mean = 17.5 +/- 0.7 sec. and GN initial mean = 11.5 +/- 1.2 sec., p<0.01) and aerobic endurance (GH initial mean = 568.5 +/- 12.2 sec. and GN initial mean = 506.8 +/- 21.7 sec., p<0.02). After 6 months of regular physical practice, hypertensive individuals continued to present worse results regarding agility, coordination and aerobic endurance (mean GH 6 months = 22.9 +/- 0.4 sec. and mean GN 6 months = 19.97 +/- 0.7 seconds; p<0.01; GH 6 months = 16.1 +/- 0.7 sec and GN 6 months = 10.6 +/- 1.3 seconds, p<0.01; GH 6 months = 498.9 +/- 20.2 sec, and GN 6 months = 555.7 +/- 11.4 seconds p<0.02, respectively). Conclusion: Hypertensive individuals have worse levels of physical fitness compared to normotensive and the practice of physical activity during the six-month period was not enough to decrease the difference between groups.
Keywords: hypertension; physical fitness; exercise